RESPON KAUM WANITA MUSLIMAH DI DESA KLAKAH KABUPATEN LUMAJANG TERHADAP HASIL PEMBUATAN JILBAB COVID INSTANT - Hidayati, Lutfiyah; TR, Imami; Nashikhah, Ma'rifatun; Kharnolis, Mein; Nahari, Inty; Arifiana, Deny (Home Economics Journal, 2021)
The corona virus pandemic is spreading very quickly, including Lumajang Regency. There are seven villages in Lumajang Regency that are included in the red zone affected by the virus. Various efforts have been socialized to the public to prevent contracting the virus, one of which is by recommending the use of personal protective equipment. The purpose of this study is to describe the response of women in Klakah Village, Lumajang to the instant Covid hijab produced by the Unesa PKM Team in the Community Service program. This research is a descriptive study carried out in October - December 2020. The number of research subjects was 50 women from Klakah village, Klakah sub-district, Lumajang Regency. Method of data collection with a questionnaire. The research instrument was in the form of a response questionnaire in the form of a Google form which was distributed through the Whatsapp social media application. The data analysis method used descriptive analysis to calculate the mean value. The results of the study stated that the response of women in Klakah village, Klakah sub-district, Lumajang to the instant covid hijab product reached an average of 91%, included in the very good criteria